Cluster of Acute Appendicitis Among High School Tibetan Students in Nanchang, China: Investigation, Control, and Prevention - Guo, Yitian; Ye, Deqiang; Yang, Guifang; Liu, Guozhen; Cui, Xiaochen; Tan, Shiyun; Guo, Yi (Frontiers in Public Health, 2022)
Objective: Infectious etiology of acute appendicitis is a current hot topic.The most of study on appendicitis came from sporadic patients and focused on clinical treatment rather than control and prevention of appendicitis in the population. The present study aims to investigate the epidemiological features of cluster of acute appendicitis, risk factors and evaluate effectiveness of control and prevention in population. Methods: We conducted longitudinal study on a cluster of acute appendicitis among Tibetan students at a high school in eastern China, which was divided into three stages:1. We retrospectively collected epidemiological data and clinical data to explore risk factor and possible transmission route in August of 2005; 2.We conducted targeted measures from August of 2005 and analyzed incidence trend from 2000 to 2010; 3. Since no new patients occurred in 2011, we conducted surveillance from the beginning of 2012 until July 2018. Results: Among 973 Tibetan students, there were 120 patients with more female patients (102 of 499, 20.4%) than male patients (18 of 474, 3.8%) from January of 2000 to December of 2010. The four-year cumulative incidence rates in female students enrolled in 2001, 2002, 2003, 2004, 2005, 2006 were 26.8% (11of 41), 27.1% (13 of 48), 44.7% (21 of 47), 42.4% (14 of 33), 23.1% (9 of 39) and 19.3% (11 of 57) respectively before their graduation. There was a clustering feature. Mutual contact with patients before the onset of symptoms was a important risk factor (Adjusted OR 4.89, 95% CI: 1.67–14.35). Transmission route may be fecal-oral infection. Before conducting targeted measures, the incidence rate increased from 2000 and peaked in 2005. After conducting targeted measures, the incidence rate decreased year by Year until 2010. Under surveillance from January of 2012 to July of 2018, only 4 sporadic patients occurred at this school. Conclusion: This cluster of acute appendicitis had features of an infectious disease in epidemiology, which can be controlled and prevented by targeted measures. Our study may also be used for prevention of sporadic patients and be generalized in general population as cluster of appendicitis occurred in many provinces of China. .